2021
DOI: 10.1038/s42003-020-01604-x
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of breathing after opioid overdose and spinal cord injury using temporal interference stimulation

Abstract: Respiratory insufficiency is a leading cause of death due to drug overdose or neuromuscular disease. We hypothesized that a stimulation paradigm using temporal interference (TI) could restore breathing in such conditions. Following opioid overdose in rats, two high frequency (5000 Hz and 5001 Hz), low amplitude waveforms delivered via intramuscular wires in the neck immediately activated the diaphragm and restored ventilation in phase with waveform offset (1 Hz or 60 breaths/min). Following cervical spinal cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 43 publications
(65 reference statements)
0
20
0
Order By: Relevance
“…Among the more promising approaches are diaphragm pacing and/ or phrenic nerve stimulation (51,(80)(81)(82). Recent preclinical reports also suggest the ability to activate spinal motor circuits via intraspinal microstimulation (83), EES (17, 21, 23, 84), and temporal interference stimulation (85), with open-or closed-loop protocols (86). However, many methods reported to date do not act as a rehabilitation strategy; continuous stimulation is needed to sustain functional improvements in breathing ability.…”
Section: Spontaneous Recovery After Cscimentioning
confidence: 99%
See 1 more Smart Citation
“…Among the more promising approaches are diaphragm pacing and/ or phrenic nerve stimulation (51,(80)(81)(82). Recent preclinical reports also suggest the ability to activate spinal motor circuits via intraspinal microstimulation (83), EES (17, 21, 23, 84), and temporal interference stimulation (85), with open-or closed-loop protocols (86). However, many methods reported to date do not act as a rehabilitation strategy; continuous stimulation is needed to sustain functional improvements in breathing ability.…”
Section: Spontaneous Recovery After Cscimentioning
confidence: 99%
“…In addition to pacing breathing, hf-EES at the cervical level below an injury was shown to potentiate phrenic motor output after cervical SCI, demonstrating that the stimulation technique can elicit at least short-term respiratory neuroplasticity (21). A similar stimulation paradigm has also been applied to the cervical cord after complete high-cervical spinal transection to activate inspiratory muscles in rats (145,146), and recently temporal interference stimulation has been used to bring about similar activation of respiratory muscles (85). Although these applications have seen limited translation to humans (17, 147), they demonstrate the feasibility of EES as a spinal cord interface capable of functional respiratory muscle activation and/or neuromodulation.…”
Section: Ees For Respiratory Neurorehabilitationmentioning
confidence: 99%
“…It was shown in rats that TI-stimulation can activate spinal motor neurons in the neck to restore breathing after opioid overdose. Again it was shown that a single sine waveform is not able to cause stimulation [5]. Furthermore, TI has been studied for retinal stimulation [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, owing to the small frequency difference (e.g., 10 Hz), the two applied fields will consequently form a temporally interfering field, with envelope modulation oscillating at the difference frequency different frequencies that can be followed by the neurons. In conventional TI stimulation methods, electrodes are placed above the scalp to convey the electric current into the brain tissue to penetrate the cranium (Grossman et al, 2017;Sunshine et al, 2021). This has raised concerns that the skin-electrode impedance could deteriorate the performance of the electric current propagation (Zaeimbashi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%